2020
DOI: 10.3390/ma13143077
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on One-Way BFRP Bar-Reinforced UHPC Slabs under Concentrated Load

Abstract: The application of fiber-reinforced polymer (FRP) bars and ultra-high performance concrete (UHPC) in the field of civil engineering is promising. An innovative FRP bar-reinforced UHPC short-ribbed bridge deck slab, with low self-weight and high structural performance, was proposed in this study. The behavior of one-way basalt FRP (BFRP) bar-reinforced UHPC slabs under concentrated load was experimentally investigated, and compared with that of a steel bar-reinforced UHPC slab. The ultimate capacity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Basalt-FRP bars have recently gained popularity among the many types of FRP materials due to their improved mechanical qualities, environmental sustainability, and costeffectiveness [10][11][12][13][14][15][16].There are still challenges associated with the use of basalt-FRP bars as reinforcement in RC slabs, such as the lack of design guidelines. Therefore, further research is needed to investigate the punching shear behavior of two-way RC slabs reinforced with basalt-FRP bars and to update design guidelines for their safe and reliable use [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basalt-FRP bars have recently gained popularity among the many types of FRP materials due to their improved mechanical qualities, environmental sustainability, and costeffectiveness [10][11][12][13][14][15][16].There are still challenges associated with the use of basalt-FRP bars as reinforcement in RC slabs, such as the lack of design guidelines. Therefore, further research is needed to investigate the punching shear behavior of two-way RC slabs reinforced with basalt-FRP bars and to update design guidelines for their safe and reliable use [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In a 2020 study, Wang et al highlighted the enhanced post-cracking rigidity and energy efficiency found in basalt-FRP grid-reinforced slabs [11]. In the same year, Xu and Hou proposed using basalt-FRP bars in ultra-high performance concrete (UHPC) slabs, which displayed better ductility despite a lower ultimate capacity compared to steel-reinforced slabs [14]. Most recently, in 2022, Shill et al compared slabs reinforced with basalt-FRP, CFRP, and steel, finding that basalt-FRP-reinforced slabs exhibited superior ductility and a more gradual decrease in load capacity beyond the peak load [15].…”
Section: Introductionmentioning
confidence: 99%
“…BFRP bars are not only used in beams, slabs, columns, and other common components [19][20][21] but are also used in the construction of concrete arch structures [22]. Tang et al [23,24] used BFRP bars instead of steel bars to make concrete arch members and found that the concrete arch with BFRP bars had comparable resistance to the concrete arch with steel bars, under air-explosion.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of new structures, researchers have proposed numerous forms of FRP-UHPC composite members. For example, UHPC beams reinforced with FRP bars [35][36][37][38], one-way BFRP bar-reinforced UHPC slabs [39], FRP fabrics reinforced UHPC panels [40], UHPC composite plates reinforced with FRP grids [41], lightweight UHPC-FRP composite decks [42], FRP bars reinforced seawater sea-sand concrete beams with a prefabricated UHPC shell [43], seawater sea-sand coral concrete-UHPC composite beams reinforced with BFRP bars [44], and so on.…”
Section: Introductionmentioning
confidence: 99%